Intervention protocol to improve scabies control in enclosed communities: a case report - A Bedoya del Campillo; N Lleopart; Ghuman ChQR; M Álvarez; M Montilla; PA Martínez-Carpio (Sociedad Española de Sanidad Penitenciaria, 2021)
Abstract Objectives To describe patients with scabies in a prison setting. Document what type of treatment was carried out. Prepare an intervention protocol to improve scabies control in the Penitentiary Center. Material and method All cases of scabies diagnosed in the Youth Detention Centre (La Roca del Vallès, Barcelona) between November 2018 and November 2019 were recorded. The treatment used was recorded. Bibliographical research on the protocols and treatment guidelines was carried out for community-acquired scabies. Results The study was performed with 762 inmates, of whom 61 patients were diagnosed with scabies. 39 patients' pathologies were detected at the time of admission to the center, 11 cases were diagnosed in the first 6 weeks after entering the prison, coinciding with the incubation period of the disease. Finally, 11 more were diagnosed when they had already been in prison for more than 6 weeks and therefore could be infected cases within the center. This parasitosis was detected mainly in inmates of North African origin, 14.7% of Algerian inmates and 14.2% of Moroccan inmates presented this pathology, compared to 1.6% among Spanish prisoners. All 61 patients were treated with permethrin and 8 cases had to repeat the treatment cycle due to apparent therapeutic failure. Research literature indicates that oral ivermectin should be the drug of first choice for the treatment of scabies in prison. Discussion The high incidence of scabies cases detected in prison led us to carry out a bibliographic review that brought about changes in the treatment protocol that may be of interest for the control of the disease in closed communities.